2003
DOI: 10.3354/cr024161
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of interpolation methods in the middle Ebro Valley (Spain): application to annual precipitation and temperature

Abstract: This paper analyzes the validity of various precipitation and temperature maps obtained by means of diverse interpolation methods. The study was carried out in an area where geographic differences and spatial climatic diversity are significant (the middle Ebro Valley in the northeast of Spain). Two variables, annual precipitation and temperature, and several interpolation methods were used in the climate mapping: global interpolators (trend surfaces and regression models), local interpolators (Thiessen polygon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
226
0
22

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 321 publications
(252 citation statements)
references
References 53 publications
4
226
0
22
Order By: Relevance
“…We demonstrated that the local and spatially complex nature of fogs makes them more difficult to map than other climatic variables such as precipitation and temperature for which it is common to obtain high R 2 values for regression models, usually higher than 0.7 (Ninyerola et al, 2007a(Ninyerola et al, , 2007b. R 2 values higher than 0.7 have been obtained previously for the Aragón region in monthly regression models of precipitation and temperature (Vicente-Serrano et al, 2003;Vicente-Serrano et al, 2007;López-Moreno et al, 2007). In contrast, fog-frequency models for this region yield R 2 values between 0.48 and 0.72 for the winter months, and only consider non-linear relationships by means of GAMs.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…We demonstrated that the local and spatially complex nature of fogs makes them more difficult to map than other climatic variables such as precipitation and temperature for which it is common to obtain high R 2 values for regression models, usually higher than 0.7 (Ninyerola et al, 2007a(Ninyerola et al, , 2007b. R 2 values higher than 0.7 have been obtained previously for the Aragón region in monthly regression models of precipitation and temperature (Vicente-Serrano et al, 2003;Vicente-Serrano et al, 2007;López-Moreno et al, 2007). In contrast, fog-frequency models for this region yield R 2 values between 0.48 and 0.72 for the winter months, and only consider non-linear relationships by means of GAMs.…”
Section: Discussionmentioning
confidence: 88%
“…Accordingly, the modelling of fog frequency is a more complex task than that of modelling other climate variables. Precipitation and mean temperature are usually well modelled in terms of elevation, aspect, influence of water bodies, and latitude (Vicente-Serrano et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations